KERJASAMA PEMERINTAH KOTA MAKASSAR DENGAN INTERNATIONAL ORGANIZATION FOR MIGRATION (IOM) DALAM PROYEK "BUILDING HEALTHY CITY" (2018-2020) - Naurah Khasanah Dwi Syafrila; Andi Meganingratna (Jurnal Dinamika Global, 2024)
This study examines how the Makassar city government collaborates with international organizations for migration (IOM) in addressing urban health challenges faced by cities with rapid urbanization such as Makassar. The Building Healthy City project is an innovative solution for the city of Makassar by utilizing technology to refocus urban health policies with expertise, resources and funds from each party involved in the project. With the implementation of paradiplomacy through maximum transnational public-private partnerships, the city government has succeeded in increasing its local capacity and providing better health services.